1987
DOI: 10.1021/bi00398a011
|View full text |Cite
|
Sign up to set email alerts
|

Complex of .alpha.-chymotrypsin and N-acetyl-L-leucyl-L-phenylalanyl trifluoromethyl ketone: structural studies with NMR spectroscopy

Abstract: A dipeptidyl trifluoromethyl ketone, N-acetyl-L-leucyl-L-[1-13C]phenylalanyl trifluoromethyl ketone, was synthesized. This compound inhibits chymotrypsin with Ki = 1.2 microM [Imperiali B., & Abeles, R.H. (1986) Biochemistry 25, 3760-3767]. The complex formed between this inhibitor and alpha-chymotrypsin was examined with 1H, 13C, and 19F NMR spectroscopy to establish its structure in solution. The keto group of the trifluoro ketone is present as an ionized hemiketal group as deduced from the comparison of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
160
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 37 publications
15
160
0
Order By: Relevance
“…However, X-ray crystallographic studies have shown that the alkylation of the active site histidine by the chloromethylketone inhibitor causes significant changes in the structure of the tetrahedral adduct compared to tetrahedral adducts which do not alkylate the active site histidine [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, X-ray crystallographic studies have shown that the alkylation of the active site histidine by the chloromethylketone inhibitor causes significant changes in the structure of the tetrahedral adduct compared to tetrahedral adducts which do not alkylate the active site histidine [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…SSHBs have been proposed as participants in the mechanisms of action of hydrolase enzymes, lyases, a ligase, and several isomerases. 16 NMR spectroscopic evidence for strong hydrogen bonding has been obtained in serine proteases, [17][18][19][20][21][22][23][24] aspartate amino transferase, 25,26 ketosteroid isomerase, 27,28 and triosephosphate isomerase 29 ( Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the significance of Asp"!# has been shown by site-directed mutagenesis [33][34][35]. Studies with some tetrahedral-intermediate models show an increase in the pK a of His&( during the catalytic process [8,16,[28][29][30], and it has been suggested that, in addition to the hydrogen bonding in the ' oxyanion hole ', the zwitterionic tetrahedral intermediate is stabilized by favourable interaction of the oxyanion with the imidazolium ion of His&( and, further, that the pK a of His&( is raised because of electrostatic\hydrogen-bond interaction with Asp"!# after substrate binding [15,16].…”
Section: Enzyme-substrate Interaction In the Catalytic Triad Of Serinmentioning
confidence: 95%
“…Liang and Abeles [30] detected an increase in the pK a of His&( ( 10) in the complex formed between α-chymotrypsin and Nacetyl--leucyl--phenylalanyl trifluoromethyl ketone. Accordingly, an increase in the pK a of His&( in a real tetrahedral adduct was also suggested.…”
Section: Enzyme-substrate Interaction In the Catalytic Triad Of Serinmentioning
confidence: 99%
See 1 more Smart Citation